The mediating role of problem solving in the relationship between emotional intelligence and mental well-being - Erdogan, Ramazan; Ozcan, Busra; Kizar, Oktay; Kizilkoca, Mustafa; Calisir, Irem Kaptangil; Bozkurt, Eyup; Kocal, Meryem (Frontiers Media Sa, 2026)
Background This study aims to examine the relationship between emotional intelligence and mental well-being among university students and to reveal the mediating role of problem-solving skills in this relationship.Methods Of these students, 707 participated, and the Emotional Intelligence Trait Scale, the Warwick-Edinburgh Psychological Well-being Scale, and the Problem-Solving Inventory were used as data collection tools. The SPSS software was used for data analysis.Results Emotional intelligence appears to have a significant effect on mental well-being, and emotional intelligence directly significantly predicts problem-solving skills, but mental well-being does not have a significant effect on problem-solving skills. Emotional intelligence appears to have a direct effect on problem-solving, and mental well-being mediates this effect. The explanatory power of the model is moderate in terms of the role of emotional intelligence in predicting mental well-being and more limited in terms of its role in predicting problem-solving skills.Conclusion In conclusion, emotional intelligence strengthens individuals' mental well-being and directly positively impacts their problem-solving skills. However, mental well-being does not play a mediating role in the problem-solving process. This suggests that the direct effect of emotional intelligence is primary in improving problem-solving skills, and mental well-being does not serve as a decisive mediating factor in this process. Therefore, interventions aimed at strengthening emotional intelligence can be effective both in enhancing individuals' mental well-being and in directly supporting problem-solving skills.
Keywords: emotional intelligence; mental well-being; problem solving; university students; mediator effect